On the Cauchy problem for a generalized Boussinesq equation - Lin, Qun; Wu, Yong Hong; Loxton, Ryan (Elsevier, 2009)
In this paper, we consider the Cauchy problem for a generalized Boussinesq equation. We show that, under suitable conditions, a global solution for the initial value problem exists. In addition, we derive the sufficient conditions for the blow-up of the solution to the problem.